Internalisasi Nilai Multikulturalisme melalui Pendidikan Islam; Interelasi Tri Sentra Pendidikan pada Masyarakat Multireligius Desa Balun Lamongan - Ahmad Hanif Fahruddin; Maskuri Maskuri; Hasan Busri (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
Balun Village community located in Turi Subdistrict, Lamongan Regency got predicate as Pancasila village. This social attribute is inherent not only because its inhabitants have theological diversity as a multi religious society, but because of their success in managing religious diversity into a harmonious and almost conflictless social order. This success story is behind this research, which aims to parse about the role of various parties in shaping the multicultural society order. This study uses qualitative method with phenomenological approach. This study successfully found, among others: 1) multiculturalism successfully internalized through various parties integrative-dialectical, both in the family environment, school and community, 2) internalized multicultural values include tolerance (tasamuh),social harmony (tawazun), mutual help (ta'awun) and moderation in religion (tawasuth),3) the process of internalization of multicultural values is carried out through two patterns both additively and transformative level. In addition, this study also found that the internalization of multicultural values goes through the stages of value transformation, value transactions and trans-internalization of values embodied through the teaching and culture of society with a tolerant attitude (tasamuh)as well as moderate( tawasuth).